Prospective inter-individual analysis of quality-adjusted life years (QALYs) in brain tumor patients: a comprehensive assessment of health preferences - Hönikl, Lisa S.; Kelm, Anna; Krieg, Sandro; Meyer, Bernhard; Butenschön, Vicki Marie (International journal of cancer, 2026)
Eloquent intracranial tumors, whether primary or secondary, are located in brain regions critical for language, motor, or sensory function. In neuro-oncology, evaluating treatment outcomes requires more than survival analysis alone. Quality-adjusted life years combine survival and quality of life, based on numerical health preference values reflecting how patients perceive specific health states. However, such data are lacking for patients with eloquent tumors. In this prospective, single-center cohort study (2016-2019), patients with eloquent brain tumors underwent standardized assessments at four time points: preoperative, postoperative, and at 3- and 6-month follow-ups. Instruments included Time Trade-Off (TTO), Standard Gamble, EuroQol 5 Dimensions (EQ-5D), and the Beck Depression Inventory (BDI). Patients indicated how many years from a 10-year life span they would trade to live in perfect health, including for hypothetical deficits like hemiparesis, aphasia, or dependency. The resulting values (range 0-1) were calculated and analyzed using Mann-Whitney U-tests. Preoperatively, 78 patients reported high quality of life (TTO median 0.9). EQ-5D index declined significantly after surgery (p < .05), while TTO and BDI scores remained stable, reflecting a deterioration in health. At 3 months (n = 23), dependency was rated as less severe compared to preoperative (p = .055; TTO 0.2 vs. 0.5), suggesting psychological adaptation. By 6 months (n = 8), health perceptions improved, indicating resilience (TTO 0.7 vs. 0.6 at 3 months). This is the first study to quantify health preferences in patients with eloquent brain tumors. While postoperative health status initially declines, resilience and adaptation occur over time, emphasizing the need for tailored postoperative care.